Semiotic Analysis on Film Industry: Case Study Suspiria Movie Poster - Raiswati Untsa Mega; Tatan Tawami (International Journal of Education, Information Technology, and Others, 2022)
Movie poster often used as a medium of commercial purposes in advertising a movie as it delivers what the movie is all. This way, film making companies could attract more viewers to see a certain movie. Therefore, the goal of this study is to analyze the message contained in the verbal and non-verbal aspects in Suspiria movie poster using semiotic approach from Barthes. This research used descriptive qualitative and literature review to collect the data. This study discusses how a movie poster from Suspiria can create and deliver its meaning to the viewer through the verbal and non-verbal aspects, which resulted in gaining interest from the potential movie viewers. The results of this study suggest that each symbol and sign (verbal and non-verbal aspects) used in the movie can covey the meaning thoroughly through its meaning association. This study concludes that the signs and symbols used in the poster movie of Suspiria has its own meaning and could represent, portray, and convey the meaning of the movie poster well.